Baseline Susceptibility and Laboratory Selection of Resistance to Bt Cry1Ab Protein of Chinese Populations of Yellow Peach Moth, Conogethes punctiferalis (Guenée) - Su Mon Shwe; Sivaprasath Prabu; Yu Chen; Qincheng Li; Dapeng Jing; Shuxiong Bai; Kanglai He; Zhenying Wang (Toxins, 2021)
Yellow Peach Moth (YPM), Conogethes punctiferalis (Guenée), is one of the most destructive maize pests in the Huang-Huai-Hai summer maize region of China. Transgenic Bacillus thuringiensis (Bt) maize provides an effective means to control this insect pest in field trials. However, the establishment of Bt resistance to target pests is endangering the continued success of Bt crops. To use Bt maize against YPM, the baseline susceptibility of the local populations in the targeted areas needs to be verified. Diet-overlay bioassay results showed that all the fourteen YPM populations in China are highly susceptible to Cry1Ab. The LC50 values ranged from 0.35 to 2.38 ng/cm2 over the two years of the collection, and the difference between the most susceptible and most tolerant populations was sevenfold. The upper limit of the LC99 estimates of six pooled populations produced >99% larval mortality for representative eight populations collected in 2020 and was designated as diagnostic concentrations for monitoring susceptibility in YPM populations in China. Hence, we evaluated the laboratory selection of resistance in YPM to Cry1Ab using the diet-overlay bioassay method. Although the resistant ratio was generally low, YPM potentially could evolve resistance to Cry1Ab. The potential developmentof resistance by target pests points out the necessity to implement resistance management strategies for delaying the establishment of pest resistance to Bt crops.